U-bend shaped turbine blade cooling passage optimization - Namgoong, H; Son, C; Ireland, P (2008)
The U-bend duct which turns flow through 180° is encountered in many engineering applications in mechanical and aerospace systems. One important example is in modern turbine blade cooling systems and, partly for this reason, the U-bend has been the subject of many fluid dynamic and heat transfer investigations. The bend flow combines many complex fluid dynamic phenomena and most of the investigations have focused on understanding of the flow physics or improving the accuracy of numerical simulations. However, reports of research into shape optimization of the U-bend are relatively sparse. The main purpose of the present investigation was to focus on finding a 3-D U-bend configuration with minimum pressure loss. The DOE (Design of Experiment) technique and surrogate design space model have been successfully applied by the authors, instead of direct optimization, to reduce computational time. Copyright © 2008 by the author(s).